Mastering Digital Media Literacy of Muslim Woman's Activists in Preventing Online Gender-Based Violence - Prima Ayu Rizqy Mahanani; Fatma Dian Pratiwi; Fartika Ifriqia; Niken Puspita Sari (Profetik: Jurnal Komunikasi, 2024)
This article tends to analyze how Muslim women's activists, who are the members of Nasyiatul Aisyiyah and Fatayat NU in Kediri and Yogyakarta, build their digital literacy to prevent violence in social media. Mainly due to the digital divide between men and women, which causes imbalance and injustice when they access digital media. The method used in data collection was semi-ethnographic, in which the researcher participated in observing research objects when carrying out activities using digital technology, interviews, and documentation on 3 members of Nasyiatul Aisyiyah and Fatayat NU, both in Jogja and Kediri. The research findings show that what has been stigmatized to women so far is that they are powerless to master information and communication technology, which does not apply to members of Fatayat NU and Nasyiatul Aisyiyah. This research shows that women are also reliable in accessing the internet for the benefit of empowering women, especially KBGO issues. This research has provided a different understanding of the phenomenon of the massive use of internet-based technology by female activists